Pro SQL server 2012 administration - Simmons, Ken (Apress, 2012)
Pro SQL Server 2012 Administration is a one-stop source for all the knowledge you'll need to professionally manage a database under Microsoft SQL Server 2012. SQL Server administration is a complex field requiring an unusually broad and well-rounded skill set. A good database administrator must be part system administrator, part database design expert, and part SQL tuning optimization guru. Above all, he or she must be capable of restoring a damaged database at any time. Database administration requires excellent people skills for dealing with management and clients, and solid technical skills for dealing with the hardware and the software. Pro SQL Server 2012 Administration addresses all aspects of database administration, regardless of the size of the implementation. Install SQL Server 2012 and create new database environments. Develop a sound backup strategy for your database. Perform recovery as needed, which many consider to be job #1. Authors Ken Simmons and Sylvester Carstarphen also help you automate your work through the use of policy-based management. Performance optimization gets good coverage, so that you can render assistance when developers need help with problem queries.  Rare among database and other technical books is solid guidance on the people side of the equation. Success as a database administrator comes from working well with others, becoming involved in the community, and building the right combination of technical knowledge and people skills to solve problems and get things done professionally and amicably. Simmons and Carstarphen pay special attention to these aspects of the job in this new edition of their comprehensive book on SQL Server administration. Helps you manage a SQL Server 2012 database at professional level Covers the gamut of database administration skills Provides guidance on performance optimization